Decoding of Happiness from Community Living Activities of the Elderly living in Saluang Subdistrict, Mae Rim District, Chiang Mai Province - Saengthong, Songserm; Wongthip, Preecha (Rajapark Journal, 2022)
The research aims to 1) study the context, concepts and processes of creating happiness from living in the community of the elderly in Saluang Sub-district, Maerim District, Chaing Mai Province. 2) Study the process of decoding happiness from living in the community of the elderly, and 3) Analyze and synthesize the pattern of decoding the happiness of the elderly. It’s qualitative research. It used a sample of 40 elderly people, a research tool 1. In-depth interviews studied the community context. Decoding happiness 2. Group conversation logs about communication in the happy living of the elderly presentation of descriptive content research. The results showed that 1) the elderly in the community had a Buddhist culture. Affects the creation of happiness from living on 4 levels 1. Happiness from the addiction to pleasant emotions. 2. Happiness from creating good things or wholesome activities 3. Happiness as a Peace of mind caused by meditation practice and 4. Happiness gets out of suffering by letting go. 2) The process of deciphering the happiness of the elderly has 4 stages, 1. Associating with a good companion or Kalyanmitra in the community 2. Learning the Principles of Buddhist Happiness 3. Apply teachings to analyze synthetics, and decipher happiness for communication. 4. Conversion of substances to daily use. and 3) The synthesis of the pattern of decoding happiness from living on two levels is 1. Samisuk or Lokiyasuk or mundane happiness is the happiness of the elderly who believe that adherence to objects and emotions satisfying the people of the world is the resulting happiness, and 2. Tiramisu or supermundane happiness, or happiness that does not require adherence to objects and pleasant emotions. It’s called Vimuttisuk, it is a letdown to achieving happiness affecting a perfect life